Media Massa, Pemerintah dan Pemilik Modal - Eko Harry Susanto (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2013)
Democratization of communication, is the starting point of mass media in promoting the achievement of a prosperous information society. But the problem, is not easy to build a democratic ideal. Because a number of people within the government still puts power in response to the message - the message conveyed by the media. On the other hand, there are still investors who interpret that identic democracy with freedom of action which is detrimental to the business is run. But democracy barriers associated with reporting transparency could have emerged from people who prefer introversion past due jargon about harmony and alignment.